Treatment of Distal Radius Intra Articular Fracture with Locking Compression Plate - Shrestha, Niraj Man; Singh, Ramesh Prasad; Chalise, Pralhad; Joshi, Kripa; Subedi, Nirajan (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Distal radius fractures are among the most common upper limb injuries, affecting both younger individuals energy trauma and older adults with osteoporosis. Achieving optimal wrist function and preventing long term complications are key goals in the treatment of distal radius fractures. Restoration of anatomical alignment is also a critical for ensuring favorable long- term outcomes. The aim of this study was to evaluate the effectiveness of locking compression plates in the treatment of distal radial intra-articular fractures.Method: This study evaluated the clinical and functional outcomes of 50 patients with distal radius intra articular fractures managed surgically with locking compression plates (LCPs) at Teaching Hospital, Jorpati between October 2011 September 2013. Open reduction and internal fixation with LCPs were included as were the clinical functional outcomes, and radiological evaluation was performed at 4 weeks, 3 months and 6 months after surgery, where Gartland and Werley and Sarmiento’s modification of Lindstrom criteria is used.Results: This study revealed that, with an average age of 32 years and an average age between 19 and 62 years, 48% (24) were classified as Frykman type IV, 28% (14) were classified as type III, 10%(5) were classified as type VI, 6%( 3) were classified as type VIII intra - articular fractures, and 4% (2) were classified as types V and VII. Forty percent (20 patients) who were treated with LCPs were excellent, and 46% (23 patients) were good.Conclusion: The outcomes are good so LCPs in the distal radius of the intra articular fractures provide stable fixation with early mobilization and excellent radiographic and functional results with a minimum complication rate.